THE EFFECT OF LEADERSHIP STYLE AND WORK MOTIVATION ON FINANCIAL PERFORMANCE AT PTPN 1 LANGSA CITY - Nasrul Kahfi Lubis (CERED Indonesia Institute, 2020)
This research aims to find out the influence of leadership style and work motivation on financial performance at PTPN 1 Kota Langsa. The sample used amounted to 84 respondents. The data analysis methods used are multiple linear regression analysis, and hypothesis proof using t test, F test, and determination coefficient analysis. Multiple linear regression analysis results obtained Y = 1.549 + 0.191X1 + 0.258X2. Adjusted R Square value is 0.664 or when percentage is 66.4%. This shows the variable leadership style and work motivation affects the financial performance at PTPN 1 Langsa City by 66.4%, while the rest by 33.6% (100% - 66.4%) influenced by other variables not studied in this study. T test results obtained that the variable leadership style and work motivation significantly affect the financial performance of PTPN I Langsa City. F test results obtained leadership style and work motivation significantly affect the financial performance of PTPN I Langsa City.